Improving elderly life: Foot exercises for blood sugar control and enhanced quality of life - Yanis Kartini; Imamatul Faizah; Iis Noventi; Aisyah Aisyah; Elly Fitriyah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Elderly people are at risk of developing degenerative diseases, one of which is diabetes mellitus. Diabetes management includes education, diet management, physical activity, and pharmacotherapy. This community service aims to determine changes in blood sugar levels after doing leg exercises to improve the quality of life of the elderly. The service participants were 51 cadres and elderly people at the Cempaka Putih Kedung Anyar Elderly Integrated Healthcare Center, Sawahan District, Surabaya City. Community service activities include; checking blood sugar levels, counseling about diabetes mellitus and foot exercise training. The success of community service is assessed based on the activeness of the elderly in doing foot exercises and a comparison of the results of checking blood sugar levels before and after being given foot exercise exercises. Before being given the leg exercise, there were 21 people (41%) whose blood sugar levels were high, and after doing the leg exercise, there was a decrease to 10 people (19.6%) who had high blood sugar levels, and almost all respondents had 80% blood sugar levels. normal. Foot exercises can lower blood sugar levels in the elderly. Regular foot exercises can maintain blood sugar levels in normal conditions. People can apply foot exercises regularly so that blood sugar levels are normal and the quality of life improves.